2013
DOI: 10.1590/s0366-69132013000100021
|View full text |Cite
|
Sign up to set email alerts
|

Adsorção de molibdato em minerais de argilas naturais e modificadas com ácido sulfúrico, ácido húmico e uréia

Abstract: ResumoSedimentos argilosos provenientes do município Assis Brasil, Acre, foram lixiviados com soluções de ácido sulfúrico, ácido húmico e uréia, visando avaliar a capacidade de retenção de molibdato nesses materiais e investigar a viabilidade do processo de adsorção na interface sólido-solução. Os materiais foram caracterizados a partir de dados de difração de raios X, espectros FTIR, cargas superfi ciais e composição química. Os modelos de isotermas de Langmuir, Freundlich e Sips foram usados no ajuste dos da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(17 reference statements)
0
1
0
1
Order By: Relevance
“…The current pandemic situation that has been caused by Coronavirus Disease 2019 (COVID-19) has increased investigation of biocidal materials that can be used to coat surfaces, which act as indirect routes of infection and spread of microorganisms, such as the coronavirus of severe acute respiratory syndrome 2 (SARS-CoV-2) [ 1 , 2 , 3 ]. Recently, studies demonstrated the feasibility of materials containing Mo in its formulation with high antimicrobial activity [ 4 , 5 ], called molybdates, which have an important role in the structure and function of metal or proteins in certain biological systems [ 6 , 7 , 8 ]. Articles have recently been published on the antimicrobial properties of silver molybdates [ 9 ], lead [ 10 ], copper [ 2 ], zirconium [ 11 ], titanium [ 12 ], iron [ 13 ], and zinc [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The current pandemic situation that has been caused by Coronavirus Disease 2019 (COVID-19) has increased investigation of biocidal materials that can be used to coat surfaces, which act as indirect routes of infection and spread of microorganisms, such as the coronavirus of severe acute respiratory syndrome 2 (SARS-CoV-2) [ 1 , 2 , 3 ]. Recently, studies demonstrated the feasibility of materials containing Mo in its formulation with high antimicrobial activity [ 4 , 5 ], called molybdates, which have an important role in the structure and function of metal or proteins in certain biological systems [ 6 , 7 , 8 ]. Articles have recently been published on the antimicrobial properties of silver molybdates [ 9 ], lead [ 10 ], copper [ 2 ], zirconium [ 11 ], titanium [ 12 ], iron [ 13 ], and zinc [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…As conchas de marisco são resíduos oriundos da maricultura, que gera diversos problemas ambientais devido à má destinação dos restos da produção, proporcionando ambientes adequados para o desenvolvimento de vetores de doenças, degradando a paisagem local, prejudicando o turismo e o comércio da região (LIMA et al, 2000;PEREIRA et al, 2013).…”
Section: Introductionunclassified